Adjustment and support needs of glioma patients and their relatives: serial interviews. Issue 6 (30th July 2012) - Cavers, Debbie; Hacking, Belinda; Erridge, Sara C.; Morris, Paul Graham; Kendall, Marilyn; Murray, Scott A.
Abstract Objective To understand factors influencing the process of adjustment to a diagnosis of glioma. Methods Twenty‐six patients and 23 relatives took part in 80 in‐depth qualitative interviews conducted at five key stages: before formal diagnosis, at start of treatment, on completion of treatment, 6 months post treatment, and post bereavement. Results High levels of distress were reported, particularly preceding and following diagnosis. Many participants described lack of specific information in the early part of their illness and a lack of clarity about what was wrong and what was going to happen next. They often desired more procedural information, as well as information about their condition and treatments available, although there was variation in the timing of when people were ready to hear this. Receiving reassurance and support was essential to patients and their relatives to help them come to terms with their illness. This need was particularly acute during the early phase of the illness when distress and uncertainty were at a peak and lessened over time as people adjusted to their illness. Conclusions Offering suitable information about what to expect early and frequently in a supportive way is much appreciated by patients. There is an important balance between ensuring that patients and their families are fully informed and fostering adaptive coping that allows for hope. Copyright © 2012 John Wiley & Sons, Ltd.